VEREDAS DO CONHECIMENTO: A ARTE DE COMPARTILHAR PRÁTICAS E EXPERIÊNCIAS NO TERCEIRO SETOR; UM ESTUDO DE CASO - Burlamaqui, Andréa Mauricio D. (2009)
The purpose of this paper is to ponder over the knowledge construction issue in the nonprofit sector, starting from the systematization of social practices and experiences, and considering, when adopted, it takes into account the characteristics of social management based upon values and organizational culture as in the search for the participation of all actors involved the social capital. It also examines (1) the origins and evolution of the third sector in Brazil and its management, (2) the concept of knowledge management and learning organizations and (3) the role of social networks on knowledge sharing. From this framework, the focus turns to the exploratory qualitative case study of a non-governmental organization (NGO) Espaço Compartilharte (EC), which achieves, in a participatory manner, the systematization of its projects. The research focuses on how the learning derived from social practice - generated between the actors that form the network of this organization - it plows shared the the source of collective knowledge. For the verification of the construction of the knowledge in the organization, the model of the spiral of the knowledge was used, as they present Nonaka and Takeuchi (1997). Although the practices of administration social Brazilians are not still products of systematized methodologies, it was ended that EC possesses a systemization model in that he/she shares learnings, it makes available tools and it builds knowledge. The results are considered pertinent to studied ONG and, therefore, you didn't generalize.